2021
DOI: 10.1097/bpo.0000000000001897
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Fusionless Surgery for Scoliosis in Spinal Muscular Atrophy: Long-term Follow-up Results in a Series of 59 Patients

Abstract: Background: Treatment of spinal muscular atrophy (SMA) scoliosis has evolved in the last decade, with the emergence of fusionless surgical techniques that allow correction of the deformity before the end of growth spurt. These techniques are expected to delay definitive spine fusion and preserve trunk growth. Purpose: The aim was to evaluate long-term clinical, radiologic, and respiratory outcomes of a minimally invasive fusionless surgery (MIFLS) in SMA scoliosis. Methods: All children affected with SMA scoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The BFC allowing further growth of the spine is therefore indicated in immature patients, as confirmed by our own study, allowing early removal of bracing, which has been demonstrated to have a negative impact on the quality of life and treatment satisfaction while not avoiding curve progression 36,37 . Furthermore, the solidity of the BFC makes final spinal fusion unnecessary, preventing further surgical interventions in skeletally mature patients, as demonstrated by long-term studies and recent meta-analyses 17,33,35 …”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The BFC allowing further growth of the spine is therefore indicated in immature patients, as confirmed by our own study, allowing early removal of bracing, which has been demonstrated to have a negative impact on the quality of life and treatment satisfaction while not avoiding curve progression 36,37 . Furthermore, the solidity of the BFC makes final spinal fusion unnecessary, preventing further surgical interventions in skeletally mature patients, as demonstrated by long-term studies and recent meta-analyses 17,33,35 …”
Section: Discussionmentioning
confidence: 55%
“…36,37 Furthermore, the solidity of the BFC makes final spinal fusion unnecessary, preventing further surgical interventions in skeletally mature patients, as demonstrated by long-term studies and recent meta-analyses. 17,33,35 From our experience, some points are worth highlighting. In the first stages of our experience with BFC, we kept both SPF and BFC for NMC based on age (younger for BFC) and general conditions (better conditions for SPF).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This technique was used in another series of 59 cases of scoliosis in spinal muscular atrophy (SMA) with the mean age at surgery of 11 years [28]. The mean preoperative body weight was 30.6 kg and 35.5 kg at the last follow up, with a mean gain of 6.1 kg at 3 years postoperatively.…”
Section: Results In Recently Published Literaturementioning
confidence: 99%
“…During the follow-up period (3 +9 years; range, 2 years to 6 +3 years), 12 mechanical complications and 16 wound infections were noted. Successful application of fusionless surgery in patients with spinal muscular atrophy was also reported [ 16 ]. The use of a growing rod may be an alternative technique for the treatment of neuromuscular scoliosis; however, a long-term follow-up study is essential to assess the outcome of the fusionless technique.…”
Section: Surgical Techniquementioning
confidence: 99%